Ответы 1

  • Решение:

    1. (cosα+ctgα)/(1 + sinα) = (cosα+cosa/sina)/(1 + sinα) =

    (sina * cosα/sina + cosa/sina)/(1 + sinα) =

    ((sina * cosα + cosa)/sina)/(1 + sinα) =

    (cosα * (sina +1)/sina)/(1 + sinα) =

    (cosα * (sina +1))/(sina * (1 + sinα) = cosa/sina = ctga;

    2. Есть формулы 1 + tg^2α = 1/cos^2α и 1 + ctg^2α = 1/sin^2α:

    cos^2α/(1 + tg^2α) - sin^2α/(1 + ctg^2α) =

    cos^2α/(1/cos^2α) - sin^2α/(1/sin^2α) =

    cos^4α - sin^4α = (cos^2α - sin^2α) * (cos^2α + sin^2α) = cos^2 (2*a).

    Ответ: 1) ctga; 2) cos^2 (2*a).

    • Автор:

      mini me
    • 3 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years